Analytical spectroscopy method development to study mechanisms of Alzheimer's and tuberculosis diseases - Beuning, Cheryle Nicole, author; Crans, Debbie C., advisor; Levinger, Nancy E., committee member; Barisas, George, committee member; Fisher, Ellen R., committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2020)
This dissertation covers the analytical method development created to study and enhance the knowledge of two specific disease mechanisms important to Alzheimer's disease and Mycobacterium tuberculosis. There are two parts in this dissertation where Part 1 is entitled Measurement of The Kinetic Rate Constants of Interpeptidic Divalent Transition Metal Ion Exchange in Neurodegenerative Disease. Part 2 is entitled The Electrochemistry of Truncated Menaquinone Electron Transporters with Saturated Isoprene Side Chains Important in Tuberculosis. These diseases appear on the World Health Organization's top 10 leading causes of death worldwide. The amyloid-beta (Aβ) peptides are associated with Alzheimer's disease, where neurodegeneration is caused by the aggregation of the peptide into senile plaques within neuronal synaptic cleft spaces. Alzheimer's disease currently has no cure due to its multi-causative pathology. One disease mechanism is the coordination of divalent metal ions to the peptide. Specifically, Aβ coordinates Cu(II) and Zn(II) ions that can enhance the aggregation of Aβ into plaques. These metal ions are highly regulated within the human body and are usually found bound to peptides and not as free ions. Therefore, the Aβ must sequester the metals from other proteins and peptides. The primary research in this dissertation advances fluorescence method development to measure interpeptidic Cu(II) exchange kinetics to be able to measure this type of disease mechanism. The small peptides GHK (Gly – His – Lys) and DAHK (Asp – Ala – His – Lys) both chelate Cu(II) with nM affinity, have biological relevance as they are motifs found in human blood like Aβ, and chelate Cu(II) with similar nitrogen-rich binding ligands as Aβ. By substituting non-coordinating lysine residues with fluorescent tryptophan, the interpeptidic exchange rates can be measured since tryptophan fluorescence is statically quenched when within 14 angstroms of a paramagnetic bound Cu(II). Thus Cu(II) transfer from Cu(H-1GHW) to either GHK or DAHK can be monitored by recovered GHW fluorescence as the Cu(II) is exchanged and second-order kinetic rate constants were determined. This methodology was then used to monitor the Cu(II) exchange from truncated Cu(Aβ1-16) and Cu(Aβ1-28) complexes to GHW and DAHW, where second-order reaction kinetic rate constants were determined. While in the exchanges between Cu(H-1GHW) with GHK/DAHK the second-order rate constants were on the magnitude of 102 or 101 M-1s-1, respectively, the exchanges from Cu(Aβ) complexes were 2-3 orders of magnitude larger, 104 M-1s-1 (to GHW and DAHW). These differences in rate constant magnitude arise from the fact that the affinity of GHW (KA = 1013 M-1) for Cu(II) is larger than Aβ (KA =1010 M-1). This method development is an important step to an accurate measurement of the interpeptidic exchange between Aβ peptides, including in their fibril and plaque formations. Since senile plaques are found in synaptic cleft spaces with nanometer distances between neurons, a model system was generated to study coordination reactions at the nanoscale. In order to do this, the metal ion would need to be released in a controlled manner. Studies of metal ion burst reactions through the use of photocages can simulate bursts of ions like those seen in the synaptic cleft. Zn(II) is often released in its ionic form within the synapse in its function as a neurotransmitter, so we simulated a burst of Zn(II) ions by using a photocage, [Zn(NTAdeCage)]- which releases Zn(II) when irradiated with light. The photocage was irradiated to release Zn(II) then we followed its reaction progress with an in situ chelator, Zincon, in reverse micelles and in bulk aqueous buffer. The coordination reaction was 1.4 times faster in an aqueous buffer than in reverse micelles, despite the Zn(II) and Zincon being closer in the nanoparticle. These observations suggested that there is an impact on coordination reactivity within a highly heterogeneous environment with a cell-like membrane, which is due to the partitioning of each ligand. We observe that the photocage stays in the water pool of the reverse micelle and the Zincon partitions into the membrane interface. Thus, the coordination reactivity is diminished, likely due to the need for Zn(II) to diffuse to the Zincon, crossing a highly organized Stern layer to encounter the Zincon. Whereas in aqueous buffer, these are free to encounter each other despite being hundreds of nanometers apart. These proof of concept studies are integral to studying initial binding dynamics of metal ions with peptides at the nanoscale present in cells and neuronal synapses. Tuberculosis is a pathogenic bacterium which despite having a curable medication, can be drug-resistant. Menaquinone (MK) analogs with regiospecific partial saturation in their isoprenyl side chain, such as MK-9(II-H2), are found in many types of bacteria, including pathogenic Mycobacterium tuberculosis and function as electron transport lipids cycling between quinone and quinol forms within the electron transport system. While the function of MK is well established, the role of regiospecific partial saturation in the isoprenyl side chain on MK remains unclear and may be related to the redox function. Recently, an enzyme in M. tuberculosis called MenJ was shown to selectively saturate the second isoprene unit of MK-9 to MK-9(II-H2). The knockout expression of this enzyme was shown to be essential to the survival of the bacterium. A series of synthesized truncated MK-n analogs were investigated using a systematic statistical approach to test the effects of regiospecific saturation on the redox potentials. Using principal component analysis on the experimental redox potentials, the effects of saturation of the isoprene tail on the redox potentials were identified. The partial saturation of the second isoprene unit resulted in more positive redox potentials, requiring less energy to reduce the quinone. While full saturation of the isoprene tail resulted in the most negative potentials measured, requiring more energy to reduce the quinone. These observations give insight into why these partially saturated menaquinones are conserved in nature.
Keywords: amyloid-beta; menaquinones; tuberculosis; interpeptidic Cu(II) exchange; Alzheimer's disease